People's willingness and determinants to use selected tele-consultation public health services in Mozambique - Germano Vera Cruz; Priscilla S. Dlamini (BMC, 2021)
Abstract Background To achieve universal health coverage by 2030, sub-Saharan African countries are planning to develop large scale tele-consultation public health services. However, there is a lack of knowledge regarding the level of peoples' willingness to use this kind of tele-health services. To address this gap and inform policymakers, the present study aims at accessing the Mozambican people's willingness to use tele-consultation public health services and the determinants associate to their willingness. Methods A total of 403 adults participated in the study. The material consisted of 32 vignettes (scenarios) describing realistic health problem situations in which an individual was proposed to use a tele-consultation public health service, varying as a function of five factors: consultation category, health problem category, health problem severity, physician category, and the consultation price. For each health problem situation presented in the vignettes, the participants were asked to rate their willingness to use the proposed tele-consultation service on an 11-point scale. A cluster analysis using the K-means procedure was applied to the quantitative raw data to capture the participants' different perspectives. ANOVA, x2 and t-test analyses were also conducted to examine the effects of the different health problem situations and the sociodemographic characteristics on the participant ratings. Results Five different perspectives (clusters) were found: never-willing (15% of the sample), severity (26%), consultation-category (22%), undecided (16%), and price-severity (21%). These perspectives were associated with participants' sociodemographic characteristics. Conclusion According to the main results, it seems that the majority of the participants (69%) were highly willing to use tele-consultation public health services in the case of mild illness, cheaper prices and follow-up consultation. In addition, the participants' willingness was significantly affected by some of the participants' sociodemographic characteristics.